"El pasado refleja el futuro": Pre-service teachers' memories of growing up bilingual. Issue 1 (2nd January 2017) - Miller, Kyle
ABSTRACT: This study examined the school memories of a cohort of bilingual pre-service teachers who experienced school as English Learners. As part of a course assignment, participants described a memory from elementary school and later used that memory to reflect on its future impact on their teaching. Data were inductively analyzed, and themes were identified that captured the struggles and promise of growing up as English Learners. The most robust themes were: (a) the vulnerability associated with school transitions, (b) embarrassing moments in the classroom, (c) English language acquisition, (d) turning points in students' education, and (e) pre-service teachers' call to teaching. Each memory-related theme was linked to anticipated dispositions and actions as bilingual teachers, as well as contrasted against the memories of pre-service teachers who experienced school as monolingual English speakers. Implications are offered for schools and practitioners.